Eco toxicity of silver nanoparticles biosynthesized by Chara sp extract and assessment of their anti-microbial activity (Funded Work) - ASMAA BAKR (International Journal of Pharma and Bio Sciences, 2019)
The present study reports biogenic synthesis of silver nanoparticles (Ag NPs) using a Chara sp. extract, determination of their eco-toxicity on phytoplankton and bioactivity against some pathogenic gram positive, negative bacteria and Candida sp. Ag NPs were characterized by UV-Vis spectroscopy, FTIR and Scanning Electron Microscopy (SEM) attached with EDX. UV-vis spectroscopy studies showed an intense absorption band at 450 nm which were further confirmed by FT-IR. The functional biomolecules reasonable for metal reduction and the interaction between the nanoparticles were identified by the Fourier transform infrared spectroscopy (FTIR) analysis. The spectrum of AgNPs from FTIR depicted the varied range of absorption from 4000–500 cm−1.The Scanning Electron Micrographs of nanoparticles in an aqueous solution showed Ag NPs had an average size of most particles ranged from 8-17.28 nm with approximately round particles with diameter 8.99nm and EDAX revealed that an absorption peak at about 3 keV confirmed presence of silver nanoparticles. This study also demonstrates an inhibitory effect of the biosynthesized Ag NPs on growth of pathogenic microbes such as Staphylococcus epidermidis, Serratiasp, Proteus vulgaris and Candida sp. Theecotoxicity of AgNPs on natural phytoplankton communities showed that there is a significant differences in Ag NPs toxicity to aquatic organisms that found in water samples (p=0.001- 0.005).Theecotoxicity of AgNPs on phytoplankton confirmed the potential accumulation and transfer of its toxicity to the next generation and released into the environment onto food webs. Also AgNPs has environmental and different pharmaceutical applications.